BASIS: A big data architecture for smart cities - Costa, Carlos (2016)
Nowadays, cities are the common choice for living, representing a complex system where governments need to perform adequately, despite current restrictions, in order to satisfy the needs of the citizens and overcome economic, social and environmental sustainability challenges. The Smart City term emerges to conceptualize the need to understand citizens, namely their services demand and their relevance in a participatory government. Smart Cities are known for their human dynamics, which makes recurrent use of permanently connected devices, frequently known as Internet of Things (IoT). Consequently, since these new cities generate a vast volume of data with significant variety and velocity, they have the potential to be one of the richest and challenging systems to generate Big Data and to benefit from its adequate storage, processing, analysis and public availability. This paper presents a Big Data architecture for Smart Cities, entitled BASIS, whose specification pays particular attention to the creation of multiple abstraction layers, from the most conceptual to the most technological, fulfilling the lack of technological detail often observed in the literature. BASIS also pays particular attention to the public availability of data. Tested in a demonstration case, the obtained results reveal adequate capability to store, process, analyse and make available Big Data in the context of Smart Cities.